1996
DOI: 10.1073/pnas.93.15.7865
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a preformed transducer complex organized by the B cell antigen receptor.

Abstract: The B cell antigen receptor (BCR) consists of the membrane-bound immunoglobulin (mlg) crosslinking, yet the pattern of protein phosphorylation is similar to that observed after BCR stimulation by antigen. The response requires cellular integrity because tyrosine phosphorylation of most substrates is not visible in cell lysates. Cells that express a BCR containing an Ig-a subunit with a mutated immunoreceptor tyrosine-based activation motif display a delayed response. The data suggest that, once expressed on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
141
1
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(157 citation statements)
references
References 41 publications
13
141
1
2
Order By: Relevance
“…S1A). The effect of pervanadate in B cells is for the most part dependent on BCR expression and its ligand-independent activity (36,37). Thus, we identify the pErk detected in immature B cells as basal, although the absolute level measured after pervanadate treatment is inflated.…”
Section: Resultsmentioning
confidence: 90%
“…S1A). The effect of pervanadate in B cells is for the most part dependent on BCR expression and its ligand-independent activity (36,37). Thus, we identify the pErk detected in immature B cells as basal, although the absolute level measured after pervanadate treatment is inflated.…”
Section: Resultsmentioning
confidence: 90%
“…In support of this view, it has been suggested that the mitogenic effects of an oncogenic truncated mutant of the epidermal growth factor receptor are due to low constitutive activation, amplified by failure to attenuate signaling (36). Interestingly, it has been proposed that a normal BCR might possess constitutive activity (11,12), and therefore this constitutive activity might be exacerbated by the absence of feedback. The mechanism leading to the absence of down-regulation is unknown.…”
Section: Discussionmentioning
confidence: 84%
“…Although there is evidence for self-aggregation of ⌬V -bearing receptors (7), it is not known whether this is required for the constitutive activity of these truncated BCR. Recently, biochemical and biological evidence has led to the suggestion that the normal BCR itself might possess constitutive activity (11,12). Constitutive activity of unligated receptors has also been postulated to explain the effects of a transgenic truncated mouse H chain and of a truncated pre-TCR (13,14), prompting us to determine whether the H chain disease protein containing BCR behaves as a normal BCR or whether the activity of the truncated BCR mimics that induced upon Ag binding.…”
mentioning
confidence: 99%
“…It is possible that tonic signals through the FcRγ-chain are required to make cells permissive to stimulation. A similar concept is illustrated by a requirement for antigen-independent tonic signals through the B-cell receptor for B-cell development (41)(42)(43). It has been suggested that isotype-switched antibodies and FcRγ expression play a role in supporting Heligmosomoides polygyrus-induced expansion of basophils (44).…”
Section: Discussionmentioning
confidence: 99%